Pulmonary artery mycotic aneurism owing to aspergillus in SARS-CoV-2 convalescent: a case report and literature review - Castillo Martinez, Daniel Benito; Palacios Rivera, Doris Michelle; Ruiz Pier, Jose Luis; Mendoza Carranza, Alvaro (International Journal of Research in Medical Sciences, 2022)
Invasive aspergillosis is a severe illness described in immune-compromised and critically ill non-immuno-compromised patients. Aspergillosis and COVID-19 co-infection cases harbor multiple unfavorable prognostic factors, with a 44% mortality versus 19% without aspergillosis. We presented the case of a 61-year-old man known with hypertension, diabetes, and smoking that went through COVID-19 infection, during the convalescent period presented multiple hemoptoic events due to A. fumigatus mycotic pseudoaneurysm, successfully resolved by selective angioembolization. Selective angioembolization is an effective alternative for high surgical risk due to comorbidities in the treatment of pulmonary mycotic aneurism.